Global patterns in leaf stoichiometry across coastal wetlands - Hu, Yu-Kun; Liu, Xu-Yan; He, Nian-Peng; Pan, Xu; Long, Song-Yuan; Li, Wei; Zhang, Man-Yin; Cui, Li-Juan (Dryad, 2020)
Aim: Coastal wetlands provide critical ecosystem functions and services,
e.g. coastal protection, nutrient retention and C sequestration. Despite
the important roles in global C, N and P cycling, the global variation in
leaf stoichiometry across coastal wetlands remains unclear. Location:
Global. Time period: 1980-2018. Major taxa studied: Vascular plants.
Methods: By compiling a global dataset of 698 data records in 205 sites,
we systematically analysed the world-wide trends and their determinants in
leaf element contents and ratios of plants across coastal wetlands.
Results: Leaf N and P contents significantly increased, but C:N, C:P and
N:P ratios decreased with increasing latitude in coastal wetlands. Mean
annual temperature was the predominant driver of leaf N, P and C:N, while
soil N:P was a good predict of leaf C:P and N:P ratios. Furthermore, N
increased faster with P in plant leaves of coastal wetlands compared to
terrestrial ecosystems. Within coastal wetlands, herb-dominated salt
marshes had significantly higher leaf P content, lower leaf N:P ratio and
lower scaling exponent of leaf N to P than tree-dominated mangroves. Main
conclusions: The similar latitudinal patterns of leaf stoichiometry in
coastal wetlands as terrestrial ecosystems reflected the similar
influences of temperature. However, different slopes of leaf P and N:P
ratios and N and P scaling relationships between these two ecosystems
suggested that different salinity and tidal inundation levels result in
different N and P use strategies in coastal wetland plants. These
differences in leaf stoichiometry between ecosystems and between different
types of coastal wetlands may need to be emphasized in future
biogeochemical modelling due to their different roles in global nutrient
and carbon cycling.
Keywords: FOS: Biological sciences